Nivel de conocimientos y actitudes del personal de enfermería en la aplicación de las medidas de bioseguridad en el servicio de cirugía A del Hospital Regional Docente de Trujillo - Briceño de la Cruz, Yuliana Judith (2015)
This research study is quantitative, descriptive - correlational, cross-sectional, the level of knowledge and attitudes of nurses was determined in implementing biosecurity measures Surgery A Regional Hospital of Trujillo during the months from October 2012 to January 2013. The sample consisted of 08 nurses and 08 nursing technicians of the surgery A. To collect data two instruments were used: Survey Biosafety Level Knowledge and attitudes of nurses in the measures biosecurity application. The information collected was processed and tabulated in SPSS for Windows version 19 statistical tests used chi - square (X 2), according to the results there is significant relationship (p <0.032) between level of knowledge and attitudes nurses in implementing biosecurity measures.